Analisis Daftar Pemilih Tetap Pemilihan Gubernur dan Wakil Gubernur menggunakan Algoritma K-Means - Syahrul Dwi Hilda; Apriade Voutama; Yuyun Umaidah (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Permanent voters list is a very large collection of data in an election. Permanent voters list data is very important for an institution related to this, one of which is a village. Lack of understanding of Data Mining at the village level is a bad thing, because Data Mining is very much needed when associated with a lot of data because one of them can make it easier to group data or clustering with the k-means algorithm which is an effective choice for clustering. In this study using the k-means algorithm clustering method supported by the RapidMiner application. Processing of permanent voter list data will be needed by institutions or related. The results of this research assisted by the rapidminer application with the k-means algorithm clustering method successfully grouped or clustering of the permanent voters list with age and address variables in institutions or those in need, especially in this study in Curug Village, Klari District, Karawang Regency.